Levels of Connection with Nature in Amazonian elder people (Research, Society and Development, 2024)
The elderly population is the fastest growing and actively participates in various socio-environmental spheres. Studying the elderly-environment relationship can reveal aspects that express the quality of life conditions in aging. Among so many aspects, the subjective bond of interaction with the natural world, called Connection with Nature (CN), that older adults can represent an indicator of comprehensive health. This study investigated NC levels among older adults in the metropolitan region of Manaus-AM, considering that older people living in the Amazon have always been very close to this coexistence with nature. Sixty-two older people between 60 years and 83 years participated (Fem=23; M=36), responding to a semi-structured interview with open and closed questions and an NC scale. The results show that most older people have high levels of NC and that nature is part of their identity even though they live in urban areas far from natural areas.